Influence of the method for determining working length on the obturation level of primary molars - Nashalie Andrade de ALENCAR; Filipe Colombo VITALI; Pablo Silveira SANTOS; Michele BOLAN; Mariane CARDOSO (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract Efficient working length determination is essential for a successful endodontic treatment. The purpose of the present study was to evaluate whether the method for determining the working length of root canals (radiographic or electronic) influences the obturation level of primary molars. Thus, a controlled, triple-blind, randomized clinical trial was conducted. Sixty-four children aged 6 to 9 years with an indication for primary molar pulpectomy were included. Participants were divided into two groups according to the method used to determine the working length of the root canals: (G1) radiographic and (G2) using an electronic apex locator. The study had 3 operators: #1 performed the clinical procedures, except the electronic measurement; #2 performed radiographic measurement and final evaluation of obturation level; and #3 performed eligibility criteria and electronic measurement. Adequacy of obturation level was evaluated based on the final conventional radiography and it was recorded as acceptable or unacceptable (short or overfilled). Data were analyzed with repeated measures logistic regression. There was no difference between the obturation level of primary molars measured by radiographic and electronic methods (p > 0.05). The other investigated variables (age, tooth type, dental arch position, last instrumentation file, and canal location) also did not influence the obturation level (p > 0.05). In conclusion, both measurement methods resulted in similar adequacy of obturation level in primary molars after pulpectomy.